Culture and the senses : bodily ways of knowing in an African community - Geurts, Kathryn Linn, 1960- (Ethnographic studies in subjectivity, 2002)
Kathryn Geurts investigates the cultural meaning system and resulting sensorium of Anlo-Ewe-speaking people in southeastern Ghana. Geurts discovered that the five-senses model has little relevance in Anlo culture, where balance is a sense, and balancing (in a physical and psychological sense as well as in literal and metaphorical ways) is an essential component of what it means to be human.